Pengaruh Financial Tecnology terhadap Manajemen Keuangan Generasi Z - Ade Irna Lestari; Fitriyani Fitriyani; Nova Apriyanti Simanungkalit; Rudi Sanjaya (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research discusses the influence of financial technology (Fintech) on the financial management of Generation Z, a generation that is familiar with digitalization and has a consumptive lifestyle. Generation Z, which accounts for around 27.94% of Indonesia's population, exhibits financial behaviors that tend to be more concerned with wants than needs. Through a literature review, this research explores how Fintech affects Generation Z's financial behavior, including the challenges that arise, such as shopping addiction and debt risk. Fintech offers easy access to financial services, such as digital payments, investments and online lending, allowing Generation Z to manage their finances more flexibly. However, their low financial literacy may result in suboptimal financial management. This study highlights the importance of financial literacy as a key factor to help Generation Z achieve sustainable financial well-being and respond to the challenges of Fintech development in the digital era